PROCESSES MONITORING DURING OPERATION OF RADIO ENGINEERING DEVICES OF FLIGHT SUPPORT - Заліський, М. Ю. (Science-based technologies, 2015)
The main current trends in theory and practice of operation of radio engineering devices for flight support in civil aviation is paying attention to the analysis possibility of the operation systems in terms of system and process approaches. Process approach involves structuring operation systems into separate processes with inputs, outputs, resources, and control actions, and these processes are somehow interconnected. It is known that all processes must occur under conditions suitable for monitoring and control. This paper considers actual scientific and technical problem of sequential engineering data processing procedures synthesis and analysis during the monitoring and conformity assessment of process constituent elements in case of radio engineering devices of flight support operation. The proposed sequential procedure for conformity assessment of operation processes can significantly reduce the duration of audits (in 1,3 – 1,6 times, on the average), and therefore, reduce material and time resources.